1985
DOI: 10.1007/bf01870660
|View full text |Cite
|
Sign up to set email alerts
|

Protamine reversibly decreases paracellular cation permeability inNecturus gallbladder

Abstract: Protamine, a naturally occurring arginine-rich polycationic protein (pI 9.7 to 12), was tested in Necturus gallbladder using a transepithelial AC-impedance technique. Protamine sulfate or hydrochloride (100 micrograms/ml = 20 microM), dissolved in the mucosal bath, increased transepithelial resistance by 89% without affecting the resistance of subepithelial layers. At the same time, transepithelial voltage (psi ms) turned from slightly mucosa-positive values to mucosa-negative values of approximately +1 to -5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 24 publications
2
34
0
1
Order By: Relevance
“…34, No. 3, 2001 Our data also show that the water secretion induced by a hypotonic buffer or a choleretic agent, forskolin, was not inhibited by protamine, an agent that blocks water movement via the paracellular pathway [27][28][29] presumably by increasing the barrier function of tight junctions, an interpretation supported by our own data showing an increase in resistance of NRC in culture exposed to protamine. Similar observations have also been made in other AQP-expressing tissues, such as proximal tubules and lung alveolar epithelium.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…34, No. 3, 2001 Our data also show that the water secretion induced by a hypotonic buffer or a choleretic agent, forskolin, was not inhibited by protamine, an agent that blocks water movement via the paracellular pathway [27][28][29] presumably by increasing the barrier function of tight junctions, an interpretation supported by our own data showing an increase in resistance of NRC in culture exposed to protamine. Similar observations have also been made in other AQP-expressing tissues, such as proximal tubules and lung alveolar epithelium.…”
Section: Discussionsupporting
confidence: 76%
“…The relevance of the paracellular pathway on water movement across the biliary epithelial barrier induced by hypotonic buffer and by forskolin was assessed by pretreatment of the IBDUs with protamine, an agent that increases the barrier function of tight junctions between epithelial cells and thus decreases the water movement across an epithelial layer via the paracellular pathway. [27][28][29] In these experiments, after 15 minutes of incubation in the isotonic KRB buffer, the enclosed and polarized IBDUs were treated with 100 g/mL of protamine chloride. After 10 minutes of incubation, the inhibitor was removed by washing IBDUs with isotonic KRB buffer.…”
Section: Effects Of Protamine On Hypotonicity and Forskolin Induced Wmentioning
confidence: 99%
“…3D). In addition, preincubation with protamine, (300 Ag/ml), which blocks the paracellular pathway in certain tissues (34), did not significantly effect water movement across BDUs (data not shown). These data show that water moves rapidly across polarized cholangiocytes into the lumen of enclosed BDUs in response to osmotic buffers by a HgCl2-inhibitable, protamineindependent process, thus reflecting a transcellular rather than a paracellular pathway.…”
mentioning
confidence: 92%
“…It has been reported that protamine increases resistance of paracellular shunt pathway in various epithelia [3, 4, 5, 6, 7, 8]. Koyama et al [6, 7, 8]reported that protamine selectively decreases cation permeability by acting mainly on the paracellular shunt pathway in the nephron segments having leaky epithelia.…”
Section: Discussionmentioning
confidence: 99%
“…Protamine has been used to characterize the paracellular shunt pathway in various epithelia including renal tubules [3, 4, 5, 6, 7, 8]. In almost all the epithelia examined so far, the paracellular shunt pathways are characterized by cation-selective permeability which is inhibited by protamine.…”
Section: Introductionmentioning
confidence: 99%